A 'means of distribution': Federico Fellini and Italian television. Issue 1 (1st January 2021) - Garofalo, Damiano; Mancinelli, Angela
This article will examine both the Fellinian imagery of television that is present in his films and the role of Fellini as a television 'critic'. In the first part, we consider Federico Fellini's entire filmography, focusing on the main cinematic texts that deal most explicitly with the world of television: Il bidone (The Swindle) (1955), La Dolce Vita (1960), Prova d'orchestra (Orchestra Rehearsal) (1979), Ginger e Fred (Ginger and Fred) (1986), Intervista (1988) and La voce della luna (The Voice of the Moon) (1989). In order to define Fellini's thoughts on television and to compare this intellectual assertiveness to traces of his own involvement with several Italian television productions, we connect the analysis of his filmography with the study of Fellini's comments, interviews and articles published in several Italian journals and magazines between the 1970s and 1980s. The aim of this article is to trace an organic relationship between Fellini and television, from the production of his films to his notes as an intellectual.